2011
DOI: 10.1063/1.3576923
|View full text |Cite|
|
Sign up to set email alerts
|

Large magnetoresistance in current-perpendicular-to-plane pseudospin valve using a Co2Fe(Ge0.5Ga0.5) Heusler alloy

Abstract: Using a newly developed highly spin-polarized Heusler alloy, Co2Fe(Ga0.5Ge0.5) (CFGG), as ferromagnetic layers, we have fabricated a current-perpendicular-to-plane pseudospin valve with large resistance change-area product (ΔRA) of 9.5 mΩ μm2 and magnetoresistance (MR) ratio (100×ΔR/R) of 41.7% at 300 K. These values were further enhanced to ΔRA=26.4 mΩ μm2 and MR=129.1% at 10 K. The large MR values are attributed to the high spin polarization of the CFGG alloy confirmed by point contact Andreev reflection mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 21 publications
1
45
0
Order By: Relevance
“…Figure 3(b) depicts the typical MR curve at 300 K of CPP-GMR device fabricated on a Si(001) substrate annealed at optimal temperature of 400 • C. Our CFGG/Ag/CFGG CPP-GMR device shows an MR ratio of 27.8% and ∆RA of 8.6 mΩ µm 2 with R p A of 29.6 mΩ µm 2 . Both the MR ratio and ∆RA value are nearly the same with those of the CFGG/Ag/CFGG CPP-GMR device grown on an MgO(001) substrate reported previously, 11,24 but much higher than those reported for the polycrystalline CPP-GMR device. More importantly, a higher MR output of Si-based CPP-GMR devices can be expected by using high spin-polarized Heusler alloys (e.g., CFMS 10 ) and new spacer layers (e.g., In-Zn-O 25 ).…”
Section: -3supporting
confidence: 64%
See 1 more Smart Citation
“…Figure 3(b) depicts the typical MR curve at 300 K of CPP-GMR device fabricated on a Si(001) substrate annealed at optimal temperature of 400 • C. Our CFGG/Ag/CFGG CPP-GMR device shows an MR ratio of 27.8% and ∆RA of 8.6 mΩ µm 2 with R p A of 29.6 mΩ µm 2 . Both the MR ratio and ∆RA value are nearly the same with those of the CFGG/Ag/CFGG CPP-GMR device grown on an MgO(001) substrate reported previously, 11,24 but much higher than those reported for the polycrystalline CPP-GMR device. More importantly, a higher MR output of Si-based CPP-GMR devices can be expected by using high spin-polarized Heusler alloys (e.g., CFMS 10 ) and new spacer layers (e.g., In-Zn-O 25 ).…”
Section: -3supporting
confidence: 64%
“…[4][5][6][7] Recently, substantial large MR ratios at room temperature (RT) were realized in fully epitaxial CPP-GMR devices with the usage of the Co-based Heusler alloys such as Co 2 MnSi (CMS), 8 Co 2 Mn(Ga 0.25 Ge 0.75 ) (CMGG), 9 Co 2 (Fe 0.4 Mn 0.6 )Si (CFMS), 10 and Co 2 Fe(Ga 0.5 Ge 0.5 ) (CFGG). 11 Such a high MR output in a low resistance device has already satisfied the MR performance required for the areal density of 2 Tbit/in 2 according to the simulation by Takagishi et al 7 However, all of these high MR outputs have only been demonstrated for the epitaxial CPP-GMR pseudospin-valves (PSVs) grown on unpractical MgO single crystalline substrates, which are too expensive for mass production and incompatible with the current semiconductor industry processes. On the other hand, for industrial viability, polycrystalline CPP-GMR devices that were grown on thermal-oxidized Si substrate have been used, [12][13][14] but unfortunately, the MR output of polycrystalline devices is much lower than those of epitaxial devices that were grown on MgO substrates.…”
mentioning
confidence: 99%
“…1 Some of the materials are half metals with a gap in the spin-polarized density of states for one spin band which should make them ideal candidates for spin-valves or magnetic tunnel junctions (MTJs). [2][3][4][5] Since the prediction by de Groot et al 6 in 1995 of a half metallic material with two inequivalent magnetic sublattices, whose moments precisely cancel, researchers have striven to fabricate such a material. While electronic structure calculations predicted several candidates, 7-9 most attempts to realize such a material had failed.…”
mentioning
confidence: 99%
“…The high spin polarization of cubic L2 1 Heusler alloys such as Co 2 MnSi, Co 2 MnGe, and Co 2 Fe(Ge 0.5 Ga 0.5 ) has been used to improve spin transfer toque efficiency, and it leads to high magnetoresistance ratios in both SVs and MTJs. [7][8][9][10][11][12][13] Recently, there has been growing interest in manganesebased compounds with the tetragonal D0 22 structure, which can be regarded as a severely distorted variant of the cubic L2 1 structure. 14,15 Alloys in the Mn 3Àx Ga series with 0 x 1 exhibit uniaxial anisotropy, and density-functional calculations indicate a high spin polarization.…”
mentioning
confidence: 99%